2013
DOI: 10.1038/srep01775
|View full text |Cite
|
Sign up to set email alerts
|

Single-atom Catalysis Using Pt/Graphene Achieved through Atomic Layer Deposition

Abstract: Platinum-nanoparticle-based catalysts are widely used in many important chemical processes and automobile industries. Downsizing catalyst nanoparticles to single atoms is highly desirable to maximize their use efficiency, however, very challenging. Here we report a practical synthesis for isolated single Pt atoms anchored to graphene nanosheet using the atomic layer deposition (ALD) technique. ALD offers the capability of precise control of catalyst size span from single atom, subnanometer cluster to nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
700
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 813 publications
(734 citation statements)
references
References 34 publications
13
700
3
2
Order By: Relevance
“…4 Using X-ray absorption fine structure analyses, they showed that the low-coordination and partially unoccupied densities of states of the Pt 5d orbitals are responsible for the excellent performance. Therefore, CO adsorption energy on atom-type Pt catalysts is generally greater than that on Pt particles and their corresponding extended surfaces.…”
Section: Co Adsorption On Carbon-supported Pt Atom and Dimermentioning
confidence: 99%
See 1 more Smart Citation
“…4 Using X-ray absorption fine structure analyses, they showed that the low-coordination and partially unoccupied densities of states of the Pt 5d orbitals are responsible for the excellent performance. Therefore, CO adsorption energy on atom-type Pt catalysts is generally greater than that on Pt particles and their corresponding extended surfaces.…”
Section: Co Adsorption On Carbon-supported Pt Atom and Dimermentioning
confidence: 99%
“…Single atom catalysts, by providing single active sites at the solid surface, exhibit many fascinating characteristics, such as high activity, selectivity, and maximum atomic utilization as compared to conventional metal catalysts. [4][5][6] In a Pt/C catalyst, the carbon support plays an important role in determining the size and degree of catalyst dispersion. Due to high surface-to-volume ratio (theoretical value of 2630 m 2 /g), graphene is a promising candidate as a substrate for stabilizing metal nanoparticles in heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally understood that the anodic peak in the reverse scan to be linked to the removal of incompletely oxidized carbonaceous species accumulated on the catalyst surface during the forward anodic scan. 2,36 CO is an intermediate species of methanol oxidation and can poison the Pt catalyst, leading to a lower fuel cell potential and energy conversion efficiency. 2 Therefore, the ratio of the forward anodic peak current density to the backward anodic peak current density (I f /I b ) can be used to indicate the CO tolerance of the catalyst.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…2,36 CO is an intermediate species of methanol oxidation and can poison the Pt catalyst, leading to a lower fuel cell potential and energy conversion efficiency. 2 Therefore, the ratio of the forward anodic peak current density to the backward anodic peak current density (I f /I b ) can be used to indicate the CO tolerance of the catalyst. [36][37][38][39] A low I f /I b value usually indicates poor oxidation of methanol to CO 2 during the forward anodic scan and excessive accumulation of residual carbon species (for example, CO) on the catalyst surface.…”
Section: Electrochemical Performancementioning
confidence: 99%
See 1 more Smart Citation